Availability Of Drugs and Logistics on Village Health and Nutrition Day in Rural and Urban Areas of South Gujarat, India - Patel, Manan J; Patel, Prakash B; Patel, N B; Bansal, R K (National Journal of Community Medicine, 2016)
Introduction: VHND session is a great opportunity for reaching to pregnant women and children less than 5 years of age. Objective of the study was to assess the status of drugs and logistics availability on Village Health and Nutrition Day (VHND) in rural areas of Tapi district and Surat city areas. Methods: This cross sectional study was conducted during September 2013 to February 2014. Out of 28 Primary Health Centres (PHCs) of Tapi district 9 were selected and out of 40 Urban Health Centres (UHCs) of Surat City, 16 were selected by random number table. Checklist of essential logistics for VHND was prepared and used to collect the data. Results: Logistics used duringAntenatal care like sphygmomanometer, stethoscope, examination table, measure tape and adult weighing scale were available at more VHND session in rural areas compared to urban session sites. Medications like iron folic acid tablets, paracetamol tablets and calcium tablets were present in more than three forth of the session at both urban as well as rural areas. Availability of Zinc tablets and cotrimoxazole tablets were very poor in urban area in contrary to rural area where they were available at almost all VHND session. Overall, logistics availability was better at rural VHND sessions in comparison to urban sessions. Conclusion: Logistics availability was poor in urban area compared to rural area. Reasons behind the same need to be explored and appropriate corrective measures need to be taken which might help to improve services provided during VHND sessions.